Digital Transformation in Human Resource Management in the Industrial Age 4.0 - Sari Sakarina; Zet Ena; Jenita; Pandu Adi Cakranegara; Susilo Surahman (Quantitative Economics and Management Studies, 2022)
The global world has entered the era of industrial revolution 4.0, which demands the speed of production flexibility and increased service to consumers. The age of the industrial revolution 4.0 has transformed various sectors into more practical and complex ones through the use of automated and digitized technology. This research aims to discover digital transformation in improving human resource management that is superior, creative, and innovative in the corporate sector. This research method uses a qualitative approach, with the type of literature review research. The data sources used are secondary data sources by reviewing journal articles and secondary data from books to support this research, all of which are by the research objectives. The results show that digital transformation will result in intense competition and compete with each other in facing the demands of industrial revolution 4.0. Therefore, the abilities and skills will result in superior performance and HR achievement